Between the northern and southern regions of Western Europe: The Acheulean site of La Grande Vallée (Colombiers, Vienne, France). (8th August 2016) - Hérisson, David; Airvaux, Jean; Lenoble, Arnaud; Richter, Daniel; Claud, Emilie; Primault, Jérôme
Abstract: Poitou is located between the Paris and Aquitaine Basins, flanked by the extensions of the Massif Central and the Armorican Massif. Many sites attributed to what in Western Europe has been termed "the Acheulean" are preserved within this region, though research has largely been limited to surface collection of material from fields and open sand quarries situated on alluvial terraces. The discovery of the site of La Grande Vallée in 1995, within the district of Colombiers in Vienne therefore provided the first opportunity to conduct a rigorous scientific examination of a stratified Pleistocene archaeological deposit. The sedimentary sequence preserved at La Grande Vallée itself (U5) has produced five archaeological layers attributable to the Acheulean. The archaeological layers contained abundant lithic remains, reflecting the in situ production of many tools, including the key tool, the biface. The large slabs of flint used gave rise to specific working methods, indicating adaptation to the raw material. Micro-wear studies have revealed that butchery activities, including slicing and chopping of meat and bone, were also carried out in situ. These observations, along with the presence of many burnt flints, suggest that this locale acted as a mixture of habitation site/workshop. Currently, thermoluminescence dates on heated flint support the geomorphological study: unit U5 appears to have been deposited between 500 ka and 400 ka. The site of La Grande Vallée is a key sequence for understanding the Acheulean of the region. The geographical position of the site at the Seuil du Poitou, between the northern and southern regions of Western Europe, makes it a reliable and insightful observation point into Middle Pleistocene settlement in Western Europe.